Reimagining cultural representation of Latinidad on the U.S. screen: this bridge called Disney - Dosch, Emily, author; Khrebtan-Hoerhager, Julia, advisor; Diffrient, D. Scott, committee member; Pedrós-Gascón, Antonio, committee member (Colorado State University. Libraries, 2023)
As one of the largest media conglomerates in the world, Disney functions as a cultural institution in its projections of mediated cultural content. Each second of their animated films operates to mold the corporation's chosen agenda. Given the salience of Disney films as creational and conformist cultural objects, I conduct a critical cultural analysis of two animation pieces, Coco (2017) and Encanto (2021). For this thesis project, I am particularly interested in the politics of representation of Latinx characters and cultures, as essential for children's understanding of the peoples and world around them. Each film, though delivered in different contexts at different times, includes common themes of the importance of family and change/migration to a new destination/generation. At the same time, the films displayed mixed successes with their interpretation, construction, and representation of Mexicanidad and Colombianiadad on the U.S. screen. These depictions were reflective and co-constructive (I argue) of the respective Mexican-American and Colombian-American interculturalities. Through such comparative critical cultural and film analysis, I hope to contribute to the existing and emerging scholarship on the representation and (mis)representation of Latinx population in Disney animated films, and in the cultural industry at large.
Keywords: Disney; Latino; Coco; representation; film